Persepsi Siswa SMA Anugrah Gloria Terpadu Terhadap Keterampilan Mengajar Mahasiswa PPL Prodi Pendidikan Matematika: persepsi keterampilan mengajar - Sutarman Borean; Mindo Hotmaida Sinambela; Yeheskiel Lolopayung; Citra Ratna Napitupulu; Christine Mersi Rumpaisum (Journal of Innovative and Creativity, 2025)
This research aims to analyze the perceptions of students at SMA Gloria Terpadu regarding the teaching skills of PPL students from the Mathematics Education Study Program at STKIP Abdi Wacana Wamena. The type and approach in this research are mixed methods. This research adopts the concurrent embedded strategy described by Creswell as part of the concurrent/embedded mixed method where the researcher collects quantitative and qualitative data simultaneously. The research sample was determined using purposive sampling techniques with specific criteria as limitations. The data collection techniques were carried out through questionnaires, interviews, and documentation. The research results show that students' perceptions of the teaching skills of PPL students from the Mathematics Education Study Program at STKIP Abdi Wacana Wamena at SMA Anugrah Gloria Terpadu are generally in the "high" category, with an average student response percentage of 82.20%. The highest percentage is in the skill of explaining lessons, which falls into the "high" category with a student response percentage of 87.86%. The lowest percentage is the skill of providing reinforcement from student responses, which is 75.71%. Therefore, PPL program students in the education field, as prospective teachers, need to enhance and develop their competencies related to reinforcement skills and implement effective variations to create a positive learning environment and motivate students.